A Conversational Implicature Analysis in the Movie “Bird Box” Directed by Susanne Bier - Sarsono, Sarsono; Abdulloh, Abdulloh; Muslim, Ikhwan; Basuki, Slamet; Silaban, Delvina (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
The research aims to show the types of conversational implicatures between the main characters in the movie Bird Box and to show the contextual meanings of conversational implicatures between the main characters in the movie Bird Box. To determine the generalized and particularized conversational implicature, the researchers employ a qualitative approach to data analysis. Watching the film for many times and recording any utterances that contain the sort of conversational implicature in a data form is how the research's data are gathered. According to the research findings, conversational implicature is present in 15 utterances. Seven of the fifteen data included generalized conversational implicature, and eight of the fifteen contained particularized conversational implicature. Malorie has four particularized conversational implicature data and seven generalized conversational implicature data. On the other hand, Tom and Jessica have two examples of particularized conversational implicature. The contextual meaning of conversational implicature amongst the main characters is also discovered by the researchers, who discover that while Jessica and Tom frequently speak explicitly in the context, Malorie tends to speak out of it